2009
DOI: 10.1007/s11250-009-9481-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of dried citrus pulp on performance, egg quality, and blood parameters of laying hens in early phase of production

Abstract: Utilization of agricultural wastes in animal nutrition is a matter of great concern. Dried citrus pulp (DCP) is a potential source of some valuable nutrients for animal and poultry. In an experiment with completely randomized design, the effect of different levels (0%, 4%, 8%, 12%, and 16%) of DCP was evaluated on performance, egg quality, and blood parameters of laying hens from 25 to 37 weeks of age. The birds were randomly allocated to five groups with six replicates and three birds in each replicate. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 12 publications
(10 reference statements)
6
29
2
1
Order By: Relevance
“…While increasing LPT up to 9% decreased (P≤0.05) the concentrate of cholesterol and triglycerides in experimental rabbit blood compared to control group. These results were agreed with Nazok and Rezaei (2010) found that using dried citrus pulp up to 16% significantly reduced triglyceride and cholesterol of laying hens. Moreover, no significant in blood cholesterol and triglyceride with broilers feeding LP up to 4.5% was observed by Nobakht (2013).…”
Section: Biochemical Analysissupporting
confidence: 92%
“…While increasing LPT up to 9% decreased (P≤0.05) the concentrate of cholesterol and triglycerides in experimental rabbit blood compared to control group. These results were agreed with Nazok and Rezaei (2010) found that using dried citrus pulp up to 16% significantly reduced triglyceride and cholesterol of laying hens. Moreover, no significant in blood cholesterol and triglyceride with broilers feeding LP up to 4.5% was observed by Nobakht (2013).…”
Section: Biochemical Analysissupporting
confidence: 92%
“…Anti-nutritional factors have significant negative effects on livestock production. These effects include reduction in palatability, digestibility and utilization of ration, intoxication of different classes of livestock, resulting in mortality or decreased production of animal and reduction in the quality of meat, egg, and milk products due to the presence of hazardous residues (Nazok et al, 2010). A number of four agro-based products are generated from fresh citrus after the main products of interest have been removed or extracted during processing or peeled for direct human consumption as in the case of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Feed intake, egg production and egg weight were not affected in laying hens fed 100 g/kg dried citrus peel in the diet (Mourao et al., ; Yang & Chung, ). Nazok, Rezaei, and Sayyahzadeh () found no adverse effects of feeding 120 g/kg citrus pulp in the diet on egg production and egg quality of laying hens. Dietary inclusion of 160 g/kg dried citrus peel was found to maintain performance (feed intake, egg production and egg quality), increase serum glucose and high‐density lipoprotein (HDL) and reduced total cholesterol, low‐density lipoprotein (LDL) and triglycerides in laying hens (Nazok et al., ).…”
Section: Dietary Recommendations Of Peel Meals For Poultrymentioning
confidence: 99%
“…Nazok, Rezaei, and Sayyahzadeh () found no adverse effects of feeding 120 g/kg citrus pulp in the diet on egg production and egg quality of laying hens. Dietary inclusion of 160 g/kg dried citrus peel was found to maintain performance (feed intake, egg production and egg quality), increase serum glucose and high‐density lipoprotein (HDL) and reduced total cholesterol, low‐density lipoprotein (LDL) and triglycerides in laying hens (Nazok et al., ). These effects may be due to the higher unsaturated fatty acid in citrus pulp as reported by Lanza et al.…”
Section: Dietary Recommendations Of Peel Meals For Poultrymentioning
confidence: 99%